Challenges in the rehabilitation of the Pusu River - Nuruzzaman, Md.; Mamun, Abdullah Al; Salleh, Md Noor (Editura Universitatea Alexendru Ion Cuza, 2017)
River rehabilitation efforts in the world are increasing to conserve the ecosystem. These efforts, generally, face challenges from various sources. Major constraints which can turn such a program into a failed project have been discussed explicitly in the first portion of this paper. In the latter portion of the paper, focus has been given on the problems of rehabilitation of the Pusu Rive at Gombak District in Malaysia. Water sampling from the river and its catchment has been done in different periods and events. Pollution loadings into the river have been calculated for different parameters. Based on analysis, sand mining activities, point source pollution and catchment landuse have been identified as the major impediments of Pusu River rehabilitation. These problems must be addressed before the rehabilitation of the river to ensure the rehabilitation of the river is successful.